2022
DOI: 10.1186/s12884-022-04690-3
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of gestational diabetes mellitus among women with polycystic ovary syndrome: a meta-analysis of longitudinal studies

Abstract: Background Previous studies have shown that polycystic ovary syndrome is a predictor of gestational diabetes mellitus, but we do not know exactly how many polycystic ovary syndrome patients may develop gestational diabetes mellitus. Currently, the incidence of gestational diabetes mellitus among women with polycystic ovary syndrome varies greatly across studies, ranged from 4.12% to 59.50%. Besides, many factors have been found to be related to the incidence of gestational diabetes mellitus amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 71 publications
0
6
0
1
Order By: Relevance
“…Many individuals with advanced MA and polycystic ovaries syndrome (PCOS) undergo ART methods to conceive. The relationship between PCOS and GDM is well established but inclusion of such individuals in studies for identification of ART-related GDM occurrence may be biased as PCOS predisposes to insulin resistance [ 43 , 44 ]. Nonetheless, results from a meta-analysis showed that the use of ART was found to be substantially higher among women with GDM, even when women with PCOS were excluded from the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Many individuals with advanced MA and polycystic ovaries syndrome (PCOS) undergo ART methods to conceive. The relationship between PCOS and GDM is well established but inclusion of such individuals in studies for identification of ART-related GDM occurrence may be biased as PCOS predisposes to insulin resistance [ 43 , 44 ]. Nonetheless, results from a meta-analysis showed that the use of ART was found to be substantially higher among women with GDM, even when women with PCOS were excluded from the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…El mecanismo del desarrollo de esta enfermedad aún no está claro, pero se sugiere que los niveles elevados de adipocinas y marcadores inflamatorios, así como el estrés oxidativo podrían exacerbar la RI. 45,46 Una de las principales complicaciones en el embarazo es la preeclampsia. Este trastorno se asocia con desórdenes endocrinológicos, la obesidad, la RI e inflamación, características que pueden presentar las mujeres con SOP.…”
Section: Discussionunclassified
“…Pancreatic insulin secretion can increase by up to 250% during pregnancy to maintain euglycemia [ 133 ]. Gestational diabetes is diagnosed if hyperglycemia develops, as defined by national and international reference ranges, and is known to be associated with increased maternal and fetal complications [ 134 , 135 ]. Hyperinsulinemia and/or hyperglycemia related to GDM or PCOS may therefore be involved in pathological placental and fetal responses.…”
Section: Mechanisms Of Action Of Nutritional Factors In the Pathophys...mentioning
confidence: 99%